PvdA congres 26-28 april 1979 RAI Amsterdam (17e Huishoudelijk congres). Van den Heuvel feliciteert Den Uyl - Slot, Lex van der, (1979)
PvdA congres 26-28 april 1979 RAI Amsterdam (17e Huishoudelijk congres). Van den Heuvel feliciteert Den Uyl.